Determinants Associated with Self-Directed Language Learning of Thai EFL Context: A Review for Future Research on Thai High School Education - Damkam, Tanadon; Chano, Jiraporn; Othman, Mohamad Khairi Haji (Universitas Negeri Makassar, 2025)
Self-directed language learning is considered as one of the most important aspect of learning process leading to individual’s success in learning and working life. The systematic review study aims to explore the determinants associated with self-directed language learning of Thai EFL context, which have been carried out for a past decade between year 2013-2023. Gough’s strategy was used as a guide for the research method. The findings of relevant research articles for this study reveal the critical determinants influencing on self-directed language learning, which include digital literacy, mindfulness meditation and practices, teachers’ roles and teaching approaches, and adversity quotients. The study discusses limitation of this study and recommends future research on implication of the relevant determinants in developing instructional innovation